Characterization of Puccinia graminis f. sp. tritici isolates derived from an unusual wheat stem rust outbreak in Germany in 2013. (12th March 2017) - Olivera Firpo, P. D.; Newcomb, M.; Flath, K.; Sommerfeldt‐Impe, N.; Szabo, L. J.; Carter, M.; Luster, D. G.; Jin, Y.
Abstract : An unusual stem rust infestation occurred in German wheat fields in summer 2013. This study analysed 48 isolates derived from 17 Puccinia graminis f. sp. tritici (Pgt) samples and six races were identified: TKTTF, TKKTF, TKPTF, TKKTP, PKPTF and MMMTF. Infection type and genotypic data confirmed that none of these races belonged to the TTKS (Ug99) race group. German isolates of race TKTTF are phenotypically different to the ones responsible for the stem rust epidemic in Ethiopia in 2013–2014. Forty isolates were genotyped using a custom SNP array. Phylogenetic analysis showed that these 40 isolates represented two distinct lineages (clade IV and clade V). Thirty‐eight isolates clustered into clade IV, which previously was defined by Ethiopian isolates of race TKTTF. Race TKKTP is of special concern due to its combined virulence to stem rust resistance genes Sr24, SrTmp and Sr1 RS A migo . The vulnerability to race TKKTP in US and international winter wheat was confirmed as 55% of North American and international cultivars and breeding lines resistant to race TTKSK (Ug99) became susceptible to TKKTP. Races identified in Germany in 2013 confirmed the presence of virulence to important resistance genes that are effective against race TTKSK. This information should be useful for breeders to select diverse and effective resistance genes in order to provide more durable stem rust resistance and reduce the use of fungicides.